Multifamily Therapy for Adolescents With School Refusal: Perspectives of the Adolescents and Their Parents - Roué, Aurélie; Harf, Aurélie; Benoit, Laelia; Sibeoni, Jordan; Moro, Marie Rose (Frontiers in Psychiatry, 2021)
Introduction: School refusal is an important public health concern in adolescent psychiatry increasing over past several years (5% of child and adolescent psychiatry consultations). Multifamily therapy has developed over thirty years. Its efficacy is validated in adult, child and adolescent psychiatry, including for children at risk of school exclusion. In this study, we aimed to explore the adolescents and their parent’s experience of a multifamily therapy treatment of school refusal with a qualitative method. Materials and Methods: This qualitative study is based on an Interpretative Phenomenological Analysis approach. We conducted 15 semi-structured interviews, participants were adolescents (n= 6) and their parents (n=9) who experienced multifamily therapy in an adolescent department in Paris. Data analysis was performed independently by two researchers. Results: For the six families, school was a source of suffering, system paralysis and social exclusion. Families reported painful emotions and separation anxiety. For teenagers, multifamily therapy increased self-confidence and allowed group experience. For parents, it gave support and relieved from feelings of stigmatization and guilt. Parents became more aware of their adolescents’ suffering and their insight. They all considered that multifamily therapy improved intra-family communication and expression of emotion. Participants highlighted the benefits of intergenerational interactions, activities, group and guidance from therapists. Discussion: Multifamily therapy uses therapeutic tools from both family therapy (joining, resonance, family competence and metacommunication) and group therapy (use of media, identity device and mirror reactions). Parents expect school solutions from multifamily therapy and question how psychiatric treatment can deal with school, school refusal being therefore understood as a social functioning disorder.